POSSIBILITIES OF USE OF FOLK PEDAGOGY IN THE FORMATION OF INDIVIDUAL AND PERSONAL CHARACTERISTICS OF STUDENTS - Jamalova Nafisa Utkirovna (Journals Park Publishing, 2022)
The article reveals the origin of folk pedagogy, its content, as well as the issues of taking into account the experience of folk pedagogy in the formation of individual personality characteristics of students and their effective use in the development and implementation of modern pedagogical principles and theories.
Keywords: culture, Uzbek people, folk pedagogy, family pedagogy, life experience, didactics, teacher-student relationship.